Java 2 micro edition application development - Kroll, Michael, 1975- (Sams, 2002)
The key to Java 2 Micro Edition (J2ME) Application Development is the clear, concise explanations of the J2ME technology in relation to the existing Java platform. This book assumes proficiency with Java and presents strategies for understanding and deploying J2ME applications. The book presents numerous real-world examples, including health care and financial sector examples from the authors' professional experience.